Analisis Laporan Keuangan Untuk Mengukur Kinerja Keuangan Pada Perusahaan Yang Go Public Di Bursa Efek Indonesia (Studi Kasus Pada PT. Indofood Sukses Makmur Tbk. Periode 2020-2022) - Dian Octama Putra; Rani Amalia; Ratih Kusumastuti (UNIVERSITAS MARITIM AMNI SEMARANG, 2023)
Analyzing the financial accounts of a firm enables one to gauge its financial standing. Ratio analysis is one of the analyses that may be done to determine wheither the company's financial state is sound. The goal of this study was to evaluate PT. Indofood Sukses Makmur Tbk's financial performance using financial ratio analysis. Descriptive analysis, which measures ratios of liquidity, solvency, profitability, and activity, is the analytical approach employed. The Indonesian Stock Exchange provided research information and statistics. According to changes in the liquidity ratio, the company's status is considered to be favorable (liquid). Thei solvency ratio demonstrates that the company's capacity to meet its financial commitments is relatively strong, indicating that the capital invested is not at risk. The activity ratio indicates an increase each year, which indicates that the business is doing well. Based on the profitability statistics, it can be concluded that the firm is still in a strong position even though there are variations from year to year.